The Forms of Hegemony in the Trajectory of the Subaltern Studies - Tarascio, Giacomo (International Gramsci Journal, 2025)
Subaltern Studies has been one of the most prominent channels in the global discussion on Gramscian concepts and their legacy, particularly concerning subalternity. A similar role can be observed with the concept of hegemony, on which—if possible—the Indian collective developed an even more distinctive approach, one that was likely more dissonant from Gramsci’s original formulation. The aim of this paper is to trace the origins and conceptual development of hegemony within the trajectory of Subaltern Studies, particularly through the writings and experience of Ranajit Guha, the collective’s leading figure and theorist. To this end, the early readings of Gramsci in India and the political-cultural formation of Subaltern Studies will be examined, followed by an analysis of how the conceptualization of hegemony evolved throughout the theoretical journey of the Indian collective.